Evaluation of nutritional status using anthropometric measurements and MQSGA in geriatric hemodialysis patients - Yigit, Irem Pembegul; Ulu, Ramazan; Celiker, Huseyin; Dogukan, Ayhan (Kare Publ, 2016)
OBJECTIVE: Malnutrition is common among hemodialysis patients and is associated with higher rates of morbidity and mortality. The aim of this study was to evaluate nutritional status of geriatric hemodialysis patients. METHODS: Total of 163 hemodialysis patients were initially screened, and 55 patients (28 males, 27 females; mean age: 72.9 +/- 8.4 years) met the criteria for inclusion. Patients were divided into 3 groups according to modified quantitative subjective global assessment (MQSGA) scores: Group I (n= 22) normal nutrition, Group II (n= 20) mild-to-moderate malnutrition, and Group III (n= 13) severe malnutrition. RESULTS: When we assessed the correlation between MQSGA nutrition score and data of malnourished patients (n= 33), positive significant correlation was found between age, C-reactive protein level, and malnutrition-inflammation score. Negative significant correlation was found between body mass index, bicep skinfold, tricep skinfold, mid-arm circumference, mid-arm muscle circumference, and phosphate and albumin levels. CONCLUSION: Malnutrition is very common and increasing with aging in geriatric hemodialysis patients. MQSGA score and anthropometric measurements can be used to assess nutritional status in geriatric hemodialysis patients.
Keywords: Anthropometric measurements; geriatric; hemodialysis; malnutrition; MQSGA